THE ROLE PLAYED BY RESILIENCE AND THE MEANING MAKING PROCESSES IN THE PERCEPTION OF STRESS AND QUALITY OF PROFESSIONAL LIFE IN A SAMPLE OF TRANSYLVANIAN HUNGARIANS - ÉVA KÁLLAY (Studia Universitatis Babes-Bolyai, 2017)
ABSTRACT. Chronic daily hassles specific to personal and occupational life have a significant negative impact on the individual's emotional and mental health, simultaneously affecting his/her subjective and psychological well‐ being, as well as quality of life. The worldwide massive changes occurring in the economic, social, personal realms become sources of chronic stress, which necessitate continuous adaptation. In such conditions, the person's resilience, and his/her capacity to confer meaning to life and work, play a critical role as protective shields in the development of functional reactions and thriving. Our present study is a continuation of our previous investigations on a Transylvanian Hungarian population, concentrating on the following major aims: (i) the investigation of the role played by resilience and meaning making in experiencing chronic stress and the work related quality of life;(ii) the investigation of the relationship between resilience and one's ability to confer meaning to life and work, necessary for the development of effective stress management programs. Our results may be salient in the development of prevention and intervention programs targeting the improvement of emotional health, subjective and psychological well‐being of Transylvanian Hungarians.